235 THROMBOLYSIS DOSING AND WEIGHT ESTIMATION IN ACUTE STROKE: A SINGLE CENTRE AUDIT. (18th November 2021) - Mannion, M; Gabr, A; Cunningham, N; Leahy, A; Paulose, S; O'Brien, I; Saleh, A; Prendiville, T; Okpaje, B; Mohamed, A; Ali, B; Ryan, R; et al.
Abstract: Background: Stroke is a leading cause of death and disability. Thrombolysis with intravenous (IV) alteplase is the mainstay management of ischaemic stroke. It has a narrow therapeutic window with a high potential for adverse outcomes such as intracranial haemorrhage. The efficacy of alteplase is time and dose dependent with weight-based dosing. National clinical guidelines recommend a dose of 0.9 mg/kg, up to a maximum of 90 mg. (Irish Heart Foundation Council for Stroke 2015). In most hospitals in Ireland however, patients are not weighed prior to thrombolysis. Time pressure and lack of available suitable equipment are factors. Methods: This retrospective clinical audit evaluated the dosing of alteplase, estimated and actual weight for a convenience sample of stroke thrombolysis patients treated between 2016–2020 at an Irish University Teaching Hospital. Results: 107 patients were audited (62 males, 45 females). Actual and estimated weights were available in 92/107. Weight was not documented (n = 15) due to severe stroke/palliative management (n = 6) or omission (n = 9). 21% (19/92) received the correct dose of 0.9 mg/kg. A further 54% (50/92) received a dose within the range of 0.81–0.99 mg/kg (±10%). 25% received a dose outside this range (> ± 10%). 11% (10/92) were under-thrombolysed and 14% (13/92) over-thrombolysed. 17/92 patients had an intracranial haemorrhage. 35% (n = 6/17) of patients who had an intracranial haemorrhage received a higher dose of thrombolysis (>10%). Conclusion: A quarter of patients received inappropriate dosing of alteplase that was outside the range of ±10% of 0.9 mg/kg. While stroke thrombolysis must be completed urgently, an accurate weight should be determined to avoid errors in dosing. A process evaluation of stroke thrombolysis would provide information on how best to incorporate an objective means of weight measurement without delaying treatment.